Rainfed altepetl : modeling institutional and subsistence agriculture in ancient Tepeaca, Mexico - López Corral, Aurelio (Archaeopress pre-Columbian archaeology, 2014)
Climate variability and human management strategies on crop stands were major factors that frequently affected agricultural yields among indigenous populations from central Mexico. This work seeks to model food production in ancient Tepeaca, a Late Postclassic (AD 1325-1521) and Early Colonial (16th century) state level-polity settled on the central highlands of Puebla, by applying a model that recognizes the presence of two independent and interconnected forms of food production: subsistence agriculture and institutional agriculture.